Business information systems : 22nd International Conference, BIS 2019, Seville, Spain, June 26-28, 2019 : proceedings.: 22nd International Conference, BIS 2019, Seville, Spain, June 26-28, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available